Elections as a means of citizens political education: A comparative study between Indonesia and Malaysia - Sunarso Sunarso; Suyato Suyato; Puji Wulandari Kuncorowati; Toba Sastrawan Manik; Ali Masykur Fathurrahman (LPMPP Universitas Negeri Yogyakarta, 2022)
The purpose of this study is to compare Indonesian and Malaysian elections in terms of (1) legal basis, (2) organizing institution, (3) implementation, (4) political party function, and (5) public participation. It was a library study using a qualitative approach. Documentation was used to gather information. The data were analyzed descriptively using the Miles and Haberman model. The data were collected, grouped, reduced, interpreted, and concluded. The data were interpreted based on concepts, theories, and critical analysis. Cross-checking was used as the data validity technique. The results of this study are (1) Indonesia has hosted 12 elections, some of which have been influenced by political dynamics, including Law No. 12 of 2003 concerning Elections for the 2004 Election, Law No. 10 of 2008, and Law No. 7 of 2017 concerning Elections. Malaysian elections are governed by two laws: (a) the Malaysian Law on General Election Deed 1958 and (b) the Malaysian Law on General Election Error Act 1954. (c) P.U.(A) 293/2002 concerning the General Election (Voter Registration) Regulation last amended by P.U.(A) 106/2012; (d) P.U.(A) 185/2003 concerning Election Regulation (Post Elections) 2003; (e) P.U.(A) 386/1981 concerning General Election Regulations (Execution of Grand Elections) 1981, last amended by P.U. (A) 134/2013. (2) General Election Commission (KPU) is the name of the election organizers, whereas General Election Institute is the name of the election organizers in the New Order Era (LPU). Suruhanjaya Choice Raya is the Malaysian election organizer (SPR) (3) The election system in Malaysia is simpler and more efficient. Malaysia uses the District Election System which is based on the location of the election district, not the population. The election system in Indonesia uses the proportional election system. (4) Malaysia is a constitutional monarchy and adheres to a parliamentary democracy system. Both Indonesia and Malaysia adhere to a multi-party system. (5) The average voter turnout in Malaysian elections is 85 percent, while voter turnout in Indonesia is only 74 percent. In general, Malaysian elections are worse than those in Indonesia. In Malaysia, election organizers tend to favor government parties. Suruhanjaya Choice Raya Malaysia (SPR) barred Diaspora residents in other nations from using the post in 2018, claiming that the Diaspora favored opposition parties.